The effects of a parasitoid wasp of a gall-making insect on host plant characteristics and the abundance of sharing host-plant herbivore - Ananto Triyogo; Hironori Yasuda (Society for Indonesian Biodiversity, 2019)
Abstract. Triyogo A, Yasuda H. 2019. The effects of a parasitoid wasp of a gall-making insect on host plant characteristics and the abundance of sharing host-plant herbivore. Biodiversitas 20: 3499-3507. The present study has evaluated the indirect, top-down effects of a parasitoid wasp, Torymus beneficus Yasumatsu et Kamijo (Hymenoptera: Torymidae), of a gall-maker, Dryocosmus kuriphilus Yasumatsu (Hymenoptera: Cynipidae), on the characteristics of the chestnut tree, Castanea crenata Siebold & Zucc. (Fagales: Fagaceae), and the implications for other herbivores, the aphid, Myzocallis kuricola (Matsumura) (Homoptera: Aphididae). sharing the same host plant. In a field experiment, the behavior of D. kuriphilus larvae on chestnut tree was influenced by the T. beneficus as indicated by a small increment of gall volume. However, parasitism did not affect certain other leaf characteristics that were induced by the gall wasp. Here we show that the characteristics of chestnut tree induced by the gall-making wasp affected M. kuricola that subsequently attacked the chestnut tree. However, the hypothesis that top-down effects by natural enemies may affect other herbivores on chestnut tree through its influence on gall-making wasp was not supported in this study. This study shows that parasitism of a gall-maker does not affect the other herbivore sharing the same host plant. Furthermore, the top-down effects of the parasitoid's behavior on plants may have different effects on sharing host herbivores that attack galled plants.